(untitled) (PANGEEA, 2025)
In Romania there are large land surfaces that are depreciated or predisposed to depreciation due to mining activity from underground or open pit. A solution regarding the technology for land depreciation controlling and preventing, in plus to the methods used at the present, can be „Stabilization cell systems”, that can be used for the settlement of slopes disposed to surface or depth erosion, but also that can be used in building of roads, railroads and hydro-technical systematizing works. In stabilizing natural and man-made channels, the Cellular Confinement Systems may be applied in a single or stacked configuration. This versatility allows the system to adapt treatments, the inherent flexibility, combined with a variety of single yet effective anchoring techniques, enables the use of both vegetated and hard-armor materials even on long, steep slopes. This paper describes the design considerations and site conditions that make Cellular. Confinement Systems a cost effective solution to typical channal/slope stabilization problems.